Exchange rate dynamics under alternative optimal interest rate rules - Mahir Binici; Yin-wong Cheung (Center for Economic Studies and ifo Institute (CESifo), 2011)
We explore the role of interest rate policy in the exchange rate determination process. Specifically, we derive exchange rate equations from interest rate rules that are theoretically optimal under a few alternative settings. The exchange rate equation depends on its underlying interest rate rule and its performance could vary across evaluation criteria and sample periods. The exchange rate equation implied by the interest rate rule that allows for interest rate and inflation inertia under commitment offers some encouraging results - exchange rate changes calibrated from the equation have a positive and significant correlation with actual data, and offer good direction of change prediction. Our exercise also demonstrates the role of the foreign exchange risk premium in determining exchange rates and the difficulty of explaining exchange rate variability using only policy based fundamentals.
Keywords: F31; E52; C52; 330; Taylor Rule; exchange rate determination; mean squared prediction error; direction of change; foreign exchange risk premium